C0079 Rehabilitative ultrasound imaging of immediate morphological changes on the upper trapezius muscle after kinesiotaping®: a randomized clinical trial. (5th July 2018) - George-Bratosin, Alexandru; Ambite-Quesada, Silvia; Fernández-Carnero, Samuel; Fernández-de-las-Peñas, César
Abstract : Background: There is evidence suggesting a clinical effect of Kinesiotaping® on the upper trapezius of individuals with neck pain; however, the underlying effect is not still understood. One potential mechanism is a mechanical effect of the Kinesiotaping® on the targeted tissue, the muscle. The assessment of changes in the upper trapezius muscle with ultrasound imaging can help to elucidate this mechanical effect. Objective: The aim of this randomized clinical trial was to investigate changes in upper trapezius and subcutaneous thickness with rehabilitative ultrasound imaging associated to changes in cervical range of motion and the related-disability in patients with neck pain. Methods: A randomized clinical trial was conducted. Thirty patients (73% female, mean age: 22±4 years) with mechanical neck pain were randomly assigned to an experimental (Kinesiotaping®) or control (sham Kinesiotaping®) group. The experimental group received Kinesiotaping® to the cervical spine according to international guideline and the placebo group received a sham Kinesiotaping® (no tension) application. Outcomes including subcutaneous thickness and muscle thickness of the upper trapezius muscle assessed with ultrasound imaging and cervical range of motion were collected at baseline and 2-days after the application of the tape by an assessor blinded to the treatment allocation of the patients. In addition, neck pain related-disability, assessed with the Neck Disability Index (NDI), was also assessed before and 1-week after the application of Kinesiotaping®. Results: No significant Group*Time interactions were observed for NDI (F=0.068, P=0.796) and cervical range of motion (F=0.053, P=0.820): both groups showed similar changes in neck pain related-disability and cervical range of motion after the application of either tape. Similarly, no significant Group*Time interactions were observed for changes in subcutaneous thickness (F=0.096, P=0.759) and muscle thickness (F=1.558, P=0.222) of the upper trapezius muscle: no significant changes were found after the application of Kinesiotaping®. Conclusions: The application of real Kinesiotaping® was not more effective than placebo (no-tensioned) Kinesiotaping® for improving neck pain related-disability and cervical range of motion in people with neck pain. Inclusion of proper tension in the Kinesiotaping® did not exert changes in ultrasound outcomes on the upper trapezius muscle.